Malaysian IP Laws: Promoting IP commercialisation and challenges - Abdul Ghani Azmi, Ida Madieha (2016)
Studies have shown the strong link between innovation and the economic performance of a country. Under the 9th Malaysia Plan and the Economic Transformation Program, innovation has been identified as the new economic driver. One of the proxy of innovation is intellectual property. Intellectual property which refers to unique, value adding creations of the human intellect that results from human ingenuity, creativity and inventiveness, is an important tool for wealth creation. The talk will explores the contribution of intellectual property created by universities to the growth of the nation's wealth. Beside national legislation on Intellectual Property, internal IP policies crafted by universities and research institutes help to shape the roadmap of the institution's R & D towards nation building. National policies such as MOSTI's IP Commercialisation Policy is also instrumental in steering the transfer of technology from universities to industry. These legal and policy instruments constitute the essential eco-system for intellectual property creation in Malaysia. To that extent, the presentation will also examine strategies that can be adopted by universities and research institutes in the management of their internal Intellectual Property assets to ensure effective creation and dissemination of knowledge. The presentation ends by looking at some of the challenges faced by universities and research institutions in their quest to bring their research outputs to the market.